Q: If r equals 5z and 15z equals 3y - then r equals?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

if r=5z and 15z =3 then r=10y

r = 5z 15z = 3y (divide by 3 to both sides) 5z = y r = y

They are: y, r, s, z and m which makes 5 of them

It equals R.

The answer depends on what R and C are.

Related questions

if r=5z and 15z =3 then r=10y

if: r = 5z 15z = 3y then: z = y/5 r = 5(y/5) r = y

r = 5z 15z = 3y (divide by 3 to both sides) 5z = y r = y

If r = 5z, then 15z = 3y, then r = y. This can be solved easily by solving for z in the second equation and substituting into the first equation.

Don't do the question immediately, read the sentence 3 times and visualize what is it saying. Its just like hitting you from the left to right brain and back to left brain again, but focus thinking on the right, its just confusing as it sounds but its just simplicity in a rather complex sentence if you did not read it carefully. Since R = 5Z then 15Z = 3Y then R = ? Since it means one R = 5Z 15Z = 3y, saying 3times the Y = 15Z So you want to find out R =?, 5Z = R, 10Z = 2Y so R = Y! :D

-3y-7=2 +7=7 _______ -10=3y 3/-10=3 r 0 y=-3

3x^2 + 3y^2 = 75 Divide both sides by '3' Hence x^2 + y^2 = 25 x^2 + y^2 = 5^2 In the Pythagorean Geometry The circle equation is x^32 + y^2 = r^2 Hence 5^2 = r^2 Hence r = 5 (The radius)

They are: y, r, s, z and m which makes 5 of them

the answer is r.

p + q + r = (2x - 9y) + (5y + 6 - 4x) + (3x + 3y - 5) = x - y + 1

I

It equals R.